Gambaran pelaksanaan program penanganan kekerasan terhadap perempuan dan anak pada Puskesmas di Yogyakarta - Rosmita Nuzuliana; Siti Istiyati (Jurnal Kebidanan, 2020)
The problem of violence against women and children (VaW/C) is a problem that requires special attention because cases of VaW/C are increasing every year. The purpose of this study was to determine the description of the management of cases of violence against children and women in Yogyakarta City Health Center. The design of this study was qualitative with data collection using in-depth interviews, the KtP / A Program Coordinator, and the implementing midwife as research subjects. Data triangulation with Psychologists and Program Coordinators and the Integrated Service Center for the Protection of Women and Children with in-depth interviews. The results of this study found that the implementation of VaW/C handling was not optimal. This is because extracting cases of violence is obtained when patients arrive, and not conducting surveys to the community. this is because the VaW/C program is not a priority for the Puskesmas work program. Violence prevention activities are carried out by socializing to the community. The facilities and infrastructure for handling cases of violence are adequate but do not have separate rooms. The implementation of VaW/C handling is in the form of physical examination and counseling. Suggestions for Puskesmas are to develop and optimize programs for handling VaW/C so that cases of VaW/C can be revealed and handled.